2021
DOI: 10.1182/bloodadvances.2020004001
|View full text |Cite
|
Sign up to set email alerts
|

Lack of differential impact of del17p on survival in African Americans compared with White patients with multiple myeloma: a VA study

Abstract: Multiple myeloma (MM) is a heterogeneous disease featured by an increased incidence in African Americans (AA). We have previously observed that with equal access to healthcare, younger AA (age <65 years) patients have superior overall survival (OS) than white patients. As MM prognosis is influenced by presence of del17p, we investigated racial differences in its occurrence and impact in a large cohort of MM patients from the Veterans Affairs (VA) system. Among 2243 VA patients with MM for whom del17p da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Collectively, these findings indicated that biological differences in MM may exist by race. For example, analyzing VA data, researchers discovered NHAA patients had a lower prevalence of the Del17p mutation, a genetic abnormality linked to poor prognosis, compared to NHW patients 18 . Some studies even found that when taking treatments into consideration, NHAA patients had better survival than NHW patients 19–21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these findings indicated that biological differences in MM may exist by race. For example, analyzing VA data, researchers discovered NHAA patients had a lower prevalence of the Del17p mutation, a genetic abnormality linked to poor prognosis, compared to NHW patients 18 . Some studies even found that when taking treatments into consideration, NHAA patients had better survival than NHW patients 19–21 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, analyzing VA data, researchers discovered NHAA patients had a lower prevalence of the Del17p mutation, a genetic abnormality linked to poor prognosis, compared to NHW patients. 18 Some studies even found that when taking treatments into consideration, NHAA patients had better survival than NHW patients. [19][20][21] Fillmore et al reported that in the veteran population, who had relatively equal access to care compared to the general population, NHAA patients aged <65 years had better survival than their NHW counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Non-Hispanic (NH) Black and Hispanic persons with multiple myeloma (MM) face multiple health-related disparities that include lower access to novel therapies and under-utilization of autologous stem cell transplantation [ 1 , 2 ]. Differences in biology may be associated with different clinical presentations and/or outcomes [ 3 , 4 ]. MM is more common in NH Black persons.…”
mentioning
confidence: 99%
“…
Non-Hispanic (NH) Black and Hispanic persons with multiple myeloma (MM) face multiple health-related disparities that include lower access to novel therapies and under-utilization of autologous stem cell transplantation [1,2]. Differences in biology may be associated with different clinical presentations and/or outcomes [3,4]. MM is more common in NH Black persons.
…”
mentioning
confidence: 99%